Sugarcane Cultivars Descriptive Fact Sheet: CP 96-1252, CP 01-1372 and CP 00-1101 - Hardev Sandhu; Wayne Davidson (EDIS)
Sugarcane cultivars CP 96-1252, CP 01-1372 and CP 00-1101 are the top three commercial sugarcane cultivars in Florida occupying >43% of total sugarcane area (400,551 acres) (VanWeelden et al. 2016). These cultivars are developed through the cooperative agreement between the United States Department of Agriculture (USDA), Canal Point, the university of Florida, Everglades Research and Education Center, Belle Glade and Florida Sugar Cane League. The purpose of this fact sheet is to provide information on these cultivars regarding their parentage, flowering, cold tolerance, yields, disease response, and any major issues with their growth or yield.